(untitled) (Experimental biology, 2019)
This review article presents and analyzes the results of completed and ongoing clinical studies of mesenchymal stem cells (MSC) as a safe and potentially effective technology for treating stroke in humans. Stroke is known to be the main cause of disability of the working population. Between a quarter and half of stroke survivors are people with significant health problems. Traditional treatments benefit only a small fraction of patients. Currently, stem cell therapy, including mesenchymal stem cells, can serve as a potential regenerative strategy for patients with neurological deficit. MSCs are known to be capable of self-renewal and differentiation into tissue-specific cells, are involved in the development, maintenance and repair of tissues, which draws attention to them as potential sources in the regenerative therapy of many diseases, including stroke. MSC, by including in the induction of angiogenesis, stimulation of neurogenesis, immunomodulation, prevention of apoptosis, can largely offset the pathological processes associated with the development of stroke. An analysis of preclinical studies examining the effects of MSC therapy after ischemic stroke shows that MSC has a beneficial effect on recovery from stroke. Key words: stroke, mesenchymal stem cells, regenerative therapy, stem cell therapy, herbal antioxidants.